Effectivenes of Gliding Exercise Therapy In Carpal Tunnel Syndrome (CTS) Patients : Literature Review - Alya Salsabila, Adhinta; Dalla Soro, Caroline Xaveriana; Nur Alpiah, Dini (Worldwide Research Publishing, 2024)
Carpal Tunnel Syndrome (CTS) is a condition characterized by pain, numbness, and tingling in the hand, particularly in the thumb, index finger, middle finger, and part of the ring finger. This condition occurs due to compression of the median nerve passing through the carpal tunnel in the wrist. This study aims to evaluate the effectiveness of gliding exercises in improving CTS symptoms and the functional status of patients. The method used is a literature review, with inclusion criteria for research articles from 2013 to 2023. The results from the five selected studies indicate that gliding exercises can significantly reduce pressure on the median nerve, thereby alleviating symptoms and enhancing the functional capacity of the hand in CTS patients. These exercises were performed once a week for 30 minutes over a period of 3 to 8 weeks, depending on the patient's condition. Gliding exercises have been proven effective as a non-medical intervention in the management of CTS, though some controversy regarding the potential risk of shifting the involved anatomical structures should be considered.